Restoration of the Intertidal Zone and Mitigation of Coastal Erosion Disasters in Sayung - Rifki Syafri; Irawati Meuraksa; Rindang Kembar Sari; Eni Kamal; Widya Prarikeslan (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
Sayung District, Demak, is a muddy alluvial coastal ecosystem that has experienced severe ecological pressure due to the massive conversion of mangrove land into ponds, which has damaged the natural function of the intertidal zone as a wave buffer and biota habitat. This study aims to: (1) Analyse changes in the coastline and loss of intertidal habitat during the period 1994–2025 using the Digital Shoreline Analysis System (DSAS); (2) Simulate land area dynamics until 2050 using System Dynamics; and (3) Assess the potential for ecosystem restoration for community economic sustainability. The simulation results show that the Hybrid Scenario (integration of mangrove greenbelts and permeable structures) provides the highest effectiveness, drastically reducing the rate of abrasion to 9.65 Ha/year by 2025. This intervention is projected to save 595.71 Ha of land from the threat of permanent submersion compared to the Business as Usual scenario. In addition to stabilising the coastline after 2030, this ecosystem restoration restores environmental services that are crucial for supporting sustainable aquaculture (silvofishery), carbon sequestration potential (Blue Carbon), and ecotourism, offering a holistic adaptation solution for coastal community resilience. Keywords: Intertidal Zone, Erosion, System Dynamics, Silvofishery, Sayung.